The Economics of Auto-Delivery: A Qualitative Exploration of Inventory Management and Profitability in Subscription Services - Permana, Ngadi; Amelia, Yessica; Rizal, Muhammad (LPPM STIE Kasih Bangsa, 2024)
This qualitative literature review examines